Bimtek Pengadaan Pupuk Organik Plus in Situ Di Desa Nyur Lembang Kecamatan Narmada Kabupaten Lombok Barat- NTB - Zaenal Arifin; Lolita Endang Susilowati; Mansur Ma’shum (Universitas Mataram, 2020)
This program is aimed to: (1) increase the knowledge of the target group on the excellence of organic fertilizers and the benefits of organic fertilizer plus application on vegetable cultivation; (2) provision of technical supervision in the production of organic fertilizers plus with decomposer of Pphosphorus fertilizers enriched with drought tolerant organism who increase phosphor solubility. The activity of community service was implemented in Nyur Lembang, Narmada, West Lombok, the Province of West Nusa Tenggara for six months (from April to September 2019) applying partisipatory approach. The activities were (1) extension on production of organic fertilizers and (2) training of production of organic fertilizers plus. The output are (1) increase of the partiipants’knowledge on the excellence of organic fertilizers and (2) the participants prosess skills in producing organic fertilizers plus in situ agricultural waste.